2021
DOI: 10.3390/life11080832
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HIT Components on the Development of Breast Cancer Cells

Abstract: Cancer cells circulating in blood vessels activate platelets, forming a cancer cell encircling platelet cloak which facilitates cancer metastasis. Heparin (H) is frequently used as an anticoagulant in cancer patients but up to 5% of patients have a side effect, heparin-induced thrombocytopenia (HIT) that can be life-threatening. HIT is developed due to a complex interaction among multiple components including heparin, platelet factor 4 (PF4), HIT antibodies, and platelets. However, available information regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This explains how the body generates platelet-activating anti-PF4 antibodies in COVID-19 patients, as detected recently [ 12 , 13 ]. Furthermore, PF4 has a high affinity to polyanions on many cell surfaces [ 34 ] such as monocytes, neutrophils, endothelial [ 31 ], and even cancer cells [ 50 , 51 ]. Thus, PF4/virus particles have a high potential to mediate and even activate platelets and other cells while PF4-antibodies are known to activate human platelets, monocytes, and neutrophils [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This explains how the body generates platelet-activating anti-PF4 antibodies in COVID-19 patients, as detected recently [ 12 , 13 ]. Furthermore, PF4 has a high affinity to polyanions on many cell surfaces [ 34 ] such as monocytes, neutrophils, endothelial [ 31 ], and even cancer cells [ 50 , 51 ]. Thus, PF4/virus particles have a high potential to mediate and even activate platelets and other cells while PF4-antibodies are known to activate human platelets, monocytes, and neutrophils [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Platelets were isolated from whole blood as previously described. 49 To test if FIT occurs, we incubated platelets with PF4, Fondaparinux, and KKO and perform experiments under both stirring-based heparin-induced platelet aggregation (HIPA) platform and at the static condition. 13 As a control, unfractionated heparin (UFH) was also tested at concentrations up to 667 μg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…We recently found that HIT components affect the development of breast cancer cell line MDA-MB-231, especially, HIT-mimicked Abs showed different effects as compared to non-HIT Abs. 45 Additionally, previous studies showed that PF4 bound monocytes, 46 human umbilical vein endothelial cells, 47 or platelets 43 allowed better binding of HIT antibodies than non-HIT ones. The negatively charged polyanions such as glycosaminoglycans (GAGs) on these cells bind to the highly positive charged PF4 that induces changes in the structure of an endogenous protein thereby expressing epitopes for HIT antibodies.…”
Section: Introductionmentioning
confidence: 99%